2022
DOI: 10.4103/jfmpc.jfmpc_396_22
|View full text |Cite
|
Sign up to set email alerts
|

Body-mass index COVID-19 severity: A systematic review of systematic reviews

Abstract: Objectives: Conflicting studies have resulted in several systematic reviews and meta-analyses on the relationship between COVID-19 and body mass index (BMI). Methods: This systematic review of systematic reviews followed an umbrella review design, and preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines; Medical literature analysis and retrieval system online (MEDLINE) and SCOPUS databases were searched for systematic reviews on the top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Early studies reported an association of worse COVID-19 outcomes with obesity and other chronic conditions such as diabetes, hypertension, cardiovascular disease, and chronic kidney disease ( 25 , 26 ). Subsequent studies found that an increased body mass index (BMI) is associated with the risk of invasive mechanical ventilation and severe COVID-19, and obesity, particularly class III obesity (BMI ≥ 40 kg/m 2 ) is associated with increased mortality ( 27 ). The risk of hospitalization also increases with increasing BMI, particularly in younger individuals (<40 years) and in those of Black ethnicity ( 28 ).…”
Section: Covid-19 and Metabolic Diseases: A Bidirectional Relationshipmentioning
confidence: 99%
“…Early studies reported an association of worse COVID-19 outcomes with obesity and other chronic conditions such as diabetes, hypertension, cardiovascular disease, and chronic kidney disease ( 25 , 26 ). Subsequent studies found that an increased body mass index (BMI) is associated with the risk of invasive mechanical ventilation and severe COVID-19, and obesity, particularly class III obesity (BMI ≥ 40 kg/m 2 ) is associated with increased mortality ( 27 ). The risk of hospitalization also increases with increasing BMI, particularly in younger individuals (<40 years) and in those of Black ethnicity ( 28 ).…”
Section: Covid-19 and Metabolic Diseases: A Bidirectional Relationshipmentioning
confidence: 99%